2014
DOI: 10.1002/hyp.10305
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the impact of temperature and humidity on the breakdown of soil water repellency in sandy soils and composts

Abstract: Soil water repellency is a widespread phenomenon with the capacity to alter hydrological and geomorphological processes. Water repellency decays with time, and the consequences are only of concern during the timescale at which the water repellency persists. This study aimed to characterize the influence of temperature and humidity on the breakdown of water repellency. Apparent contact angle measurements were carried out on samples consisting of sand treated with stearic acid as well as naturally repellent dune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…In natural soils, repellency often breaks down at high water contents (de Jonge et al, ), so the reduced ability to condense water vapor may represent a positive feedback by which hydrophobic conditions are maintained even in relatively humid conditions. This mechanism may also pertain to previous observations showing that air humidity and liquid solid‐water contact angles were positively correlated (i.e., greater contact angles were observed at higher air humidity; Whelan et al, ). Still, the Whelan et al () study observed this relationship for sand particles that had been treated with SA yet not in natural dune sand particles, meaning that these results could be artifacts arising from the use of pure minerals and hydrophobicity‐inducing chemicals.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In natural soils, repellency often breaks down at high water contents (de Jonge et al, ), so the reduced ability to condense water vapor may represent a positive feedback by which hydrophobic conditions are maintained even in relatively humid conditions. This mechanism may also pertain to previous observations showing that air humidity and liquid solid‐water contact angles were positively correlated (i.e., greater contact angles were observed at higher air humidity; Whelan et al, ). Still, the Whelan et al () study observed this relationship for sand particles that had been treated with SA yet not in natural dune sand particles, meaning that these results could be artifacts arising from the use of pure minerals and hydrophobicity‐inducing chemicals.…”
Section: Discussionsupporting
confidence: 71%
“…This mechanism may also pertain to previous observations showing that air humidity and liquid solid‐water contact angles were positively correlated (i.e., greater contact angles were observed at higher air humidity; Whelan et al, ). Still, the Whelan et al () study observed this relationship for sand particles that had been treated with SA yet not in natural dune sand particles, meaning that these results could be artifacts arising from the use of pure minerals and hydrophobicity‐inducing chemicals. Similar caution may be warranted when extending the findings of the present study, which used model minerals, to natural soils.…”
Section: Discussionsupporting
confidence: 71%
“…Because of complicated biological, physical and chemical processes like soil respiration, soil evaporation, plant transpiration and so on, soil temperature and moisture have a close dynamic relationship with each other. Therefore, in order to better control and predict the hydrothermal conditions of a wheat-soil system, models simulating soil moisture-heat coupling need to be established (Perez et al 2013;Whelan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because of complicated biological, physical and chemical processes like soil respiration, soil evaporation, plant transpiration and so on, soil temperature and moisture have a close dynamic relationship with each other. Therefore, in order to better control and predict the hydrothermal conditions of a wheat-soil system, models simulating soil moisture-heat coupling need to be established (Perez et al 2013;Whelan et al 2015).…”
Section: Introductionmentioning
confidence: 99%